A evolução do spread bancário brasileiro na última década: uma investigação empírica dos seus determinantes - Carvalho, Ranério Noronha de (2013)
The unprecedented growth in the Brazilian credit market in recent years made it possible to reach an impressive level of its GDP. This fact is surely related to economic development experimented by the country in current years. Within this scenario, the price which is charged in credit operations started to play a fundamental role to the maintenance of sustainable growth. Thus, the bank spreads which mean the difference between the interest rate charged to borrowers and the funding cost of funds deposited at financial institutions – also began to be disputed in virtue of their actual high level state. The goal of this work is to evaluate the Brazilian banking spread sector evolution in the last decade and empirically investigate its determinants. Therefore, it may employ tools such as the so-called Vectors Autoregressive in order to figure out and work out the main variables which are related to spread regarding the 2000-2012 period. Making use of impulse-response functions, one intends to show that inflation is one of the main macroeconomic determinants to the Brazilian spread.